The Temporal World in Caregivers of Cancer Survivors: Intertextual Analysis of their Experiences about the Perception of Time Compared with Excerpts from the Book "Einstein's Dreams - Vargas, Rafael; Camargo, Andrés (Journal of Family Medicine, 2019)
Purpose: The perception of time and its measurements depend on subjective constructs that vary according to changes in health. The evidence has shown that cancer diagnosis induces new relationships with time in patients and caregivers. The purpose of this study was to propose a multifaceted view about time perception referred by caregivers of cancer survivors. Methods: This study used a qualitative phenomenological methodology including semi-structured interviews with caregivers of cancer survivors. Transcripts of the interviews were analyzed using an approach for intertextual analysis, taking as reference the book "Einstein's dreams". Results: The analysis of transcripts shows changes caregivers’ time perception. Participants were grouped into three essential moments related to each stage of the disease. The variations found in the perception of time in caregivers can be explained by common physiological and behavioral responses associated with the diagnosis of a chronic disease (i.e. stress, anxiety, fear, unhappiness, and sadness), which can be modified in the course of the disease. Conclusions: We propose that a holistic approach to patient and caregiver care should include management of time perception, thus establishing interventions that facilitate a change in the experience of time perception into a more pleasant experience after a cancer diagnosis. The above may result in increased quality of patient care and possibly increased quality of life of caregivers.
Keywords: Time perception; Caregivers; Cancer; Narrative medicine; Intertextual analysis.